Theoretical Calculation and ADAMS Simulation of RV Reducer Operating Frequency - Xu Honghai; Wang Wentao; Liu Xueao; Feng Yubing (Jixie chuandong)
The theoretical formulas of operating frequency are established based on transmission principle and operation mode of RV reducer by using mechanism transformation method and pure rolling hypothesis of bearing roller,and applied to calculating operating frequency of RV- 40 E reducer. The theoretical calculated results are checked by ADAMS simulation,the maximum error of theoretical values is only 4. 19 percent. The autorotation speed of crank throw bearing roller is very high,increasing the roller diameter of crank throw bearing is an effective way to lower roller autorotation speed and improve bearing life. A general,quick and efficient calculating method for rotational frequency of RV reducer transmission parts and rolling bearing parts is provided.